Perfilhamento e valor nutritivo de pastagens de capins marandu e xaraés[BRACHIARIA BRIZANTHA (HOSCHST EX A. RICH.) STAPF.] sob manejo intermitente e doses de nitrogênio e potássio - AMARAL, Alliny das Graças (2010)
The pastures are formed by a population of plants and each plant is formed by basic units called tillers. Management practices allow the knowledge of the processes of tillering. The nutritional value of pasture is determined by chemical composition of the plant and its digestibility may be affected by nutrient supply, the station year and the grazing management. An experiment was conducted at Embrapa Rice and Beans-Midwest Center for Dairy Research, in order to evaluate the tillering and nutritive value of grasses and Marandu Xaraés fertilized with nitrogen (N) and potassium (K) (0, 100, 200 and 300 kg / ha / year), from December 2007 to May 2008. The experiment was complete block design with three replications. Data Tiller were grouped in four seasons during the trial period for the variable tiller density (DPP) and three times for other variables (TAP, TSP, and TMP IEP). The evaluation of tillering was held in an area demarcated by tillers known. From the initial population, each grazing were identified new populations of tillers, marked with different colored wires. For the value data nutrition were evaluated in the dry season and water. The collection of samples was performed by simulated grazing were analyzed and the CP, NDF, ADF, lignin and IVDMD. In the review of DPP, there were dose effect (P = 0.0510) and age (P <0.0001), and after the grazing periods, the DPP is stabilized. No differences were found between seasons for the rate of tillers (TAP) to treat 300 kg of N and K / ha / year. In rainy season, the mortality rate of tillers (TMP) were lower the dose of 300 kg N and K / ha / year. The survival rate of tillers (TSP) was higher in water at a dose of 300 kg N and K / ha / year and 200 kg of N and K / ha / year, not different from the other doses. The stability index of tillers (IEP) remained above 1.0 in all treatments and times. For capimxaraés, the linear increase in fertilizer levels stimulated tillering with the increase in DPP to 300 kg of N and K / ha / year. Waters, the dose of 100 kg of N and K / ha / year showed higher TAP. The other doses and times not differed. In the waters between 0 and 100 kg of N and K / ha / year yielded the highest TMP. However, the dose of 100 kg of N and K / ha / year did not vary from 200 kg N and K / ha / year, with intermediate values. At a dose of 300 kg of N and K / ha / year were observed the lowest TMP. It was observed that the pastures fertilized 300 kg of N and K / ha / year had the highest TSP in relation to too, for the waters. The highest values were found in the TSP dry seasons. The stability index of tillers (IEP) remained above 1.0 in all treatments and times. At a dose of 300 kg of N and K / ha / year was observed the highest TSP during the rainy season, although the highest values have been in the dry season. The NDF, ADF and lignin were not influenced by fertilization, but the ADF (33.40 and 31.20% respectively) and lignin (3.93% and 2.97, respectively) were higher in the rainy season. The average CP of pastures were not affected by fertilization, except for CP content pastures fertilized with 200 kg N and K / ha / year was higher (P = 0.0353) during the rainy season. The concentration of NDF pastures fertilized with N were 7.7 and 7.1% lower (P = 0.0368) than Unfertilized, in times of rainy and dry seasons, respectively. The levels Average ADF were not affected by fertilization, but the average content FDA pastures in the rainy season was lower (P = 0.0933) than during the drought. The average content of lignin pastures fertilized with 200 kg of N and K / ha / year was higher (P = 0.0547) than in pastures fertilized with 100 N and K / ha / year (2.27 and 3.86% respectively). The average IVDMD of pasture was higher Unfertilized (P = 0.0476) than that of pastures fertilized with 200 kg of N and K / ha / year, and in rainy season, the IVDMD of pasture was not fertilized greater than that of fertilized pastures. In the pastures fertilized with 300 kg of N and K / ha / year, IVDMD in the rainy season was higher (P = 0.0155) than in the dry season. Pastures xaraés unfertilized grass are prone to susceptibility degradation in the short term and it is recommended fertilization rates above 200 kg N and K / ha / year. Grazing management based on light interception proved valid for pastures that receive manure. Pastures are fertilized more stable compared to the dynamics of tillering. There was no variation IVDMD significantly due to fertilization rates and periods studied with always harvested forage in the same physiological maturity. When the pasture was managed based on IL fertilization affected only the CP. Fertilization did not affect the nutritional value of grass xaraés subjected to grazing management IL-based.